Domain Public Payant Model On Used Of TCEs For Creative Economic Development In Indonesia - Ariy Khaerudin (JURNAL PENELITIAN SERAMBI HUKUM, 2021)
Government policies in developing the economy as raw material for creative economy. The political law of the government is then set out in a presidential regulation governing cultural heritage (including Traditional Cultural Expression/TCEs) as a strategy in the development of the creative economy. However, it is feared that it will increasingly leave the interests of traditional communities as the owner of TCE rights. The approach in this paper uses the study of literature using primary and secondary data. The results of the study need to balance the interests of individual economic actors with traditional society by maintaining the atmosphere by synchronizing or harmonizing supporting legislation. The model of using first pay can then be used as a basis and help the creative economy entrepreneurs in running a business so that it can contribute revenue to the State. Keywords: Domain Public Payant, Folklore, creative, economic